Acute fatty liver of pregnancy: a diagnostic challenge to obstetrician - Nayak, Kavitha D.; Nambiar , Jayaraman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Vomiting is a common symptom in pregnancy. However, vomiting in third trimester could be due to uncommon causes. One of the rare causes being acute fatty liver of pregnancy which is life threatening. Here we present an interesting case report and the importance of timely diagnosis of acute fatty liver of pregnancy.